A Rare Case of Neurofibromatosis Type 1 with Multiple Primary Tumors: A 29-Year Disease Course - Shafna Saif, Hamna Saif (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Neurofibromatosis Type 1 (NF1) is an autosomal dominant disorder affecting 1 in 3,000 individuals and predisposing patients to both benign and malignant neoplasms. While cutaneous neurofibromas and optic pathway gliomas are commonly observed, the development of multiple, distinct, and aggressive primary tumors across organ systems is exceedingly rare. Objectives: To report a rare case of NF1 presenting with three primary tumors over 29 years and highlight the need for standardized surveillance in NF1 patients. Materials and Methods: This case report was conducted at a tertiary care hospital and involved a longitudinal follow-up of a single female patient with neurofibromatosis type 1 (NF1) from 1995 to 2024. The patient included in the report had a confirmed diagnosis of NF1 with histopathologically verified tumors. Data were obtained retrospectively through a detailed review of medical records, imaging studies, and biopsy reports. Since the study focused on a single case, the analysis was descriptive in nature and aimed at documenting the clinical course, tumor progression, and management over nearly three decades of follow-up. Results: At age 29, the patient developed angiosarcoma in the left arm, confirmed histologically after surgical excision. Recurrence necessitated multiple resections and radiotherapy. At age 55, she presented with rectal bleeding; colonoscopy revealed bleeding colonic polyps managed via coiled embolization. At 59, the patient developed seizures and cognitive decline; neuroimaging revealed a space-occupying lesion. Biopsy confirmed glioblastoma multiforme, leading to rapid deterioration and death within 10 days. No systemic surveillance had been conducted between tumor events. Conclusion: This case underscores the unpredictable and multisystemic nature of NF1, exemplifying the risk of multiple life-threatening tumors over time. It highlights the urgent need for a structured, multidisciplinary surveillance protocol incorporating neurologic, oncologic, dermatologic, and gastrointestinal evaluations. Proactive and early screening could have facilitated timely interventions and may have significantly altered the patient's clinical outcome. Lifelong monitoring is essential to improve prognosis and survival in NF1 patients. Keywords: Neurofibromatosis 1, Glioblastoma, Angiosarcoma, Colonic Polyps, Multisystem Tumors